Sustainable profitability of ethical and conventional banking - Ricardo Costa-Climent; Carla Martínez-Climent (Contemporary Economics, 2018)
In recent years, social movements have echoed calls for greater social and environmental responsibility. Although financial institutions promote development, consumers have lost confidence in banks. As we enter the Fintech era, banks have the opportunity to use new tools that enable greater transparency for customers. Corporate social responsibility (CSR) plays a key role in increasing social awareness of regulators, society, shareholders, and employees-in short, stakeholders. This study therefore focuses on banks that have designed their activities and investments to contribute to sustainability. The principal contribution of this paper is to show the existence of a range of business models that arise following different responses by different types of banks. These different responses occur because the primary objective of sustainable banks is to meet the needs of stakeholders and contribute to sustainable development, whereas conventional banks simply apply and execute CSR policies. It is possible to differentiate between ethical banks and commercial banks. To ensure economic progress and achieve sustainability, it is fundamental to balance economic profitability with people's social and environmental aspirations.
Keywords: G21; Q01; Q56; 330; ethical banking; sustainable banking; corporate social responsibility; CSR; fintech